Electrocardiographic veterinary clinic of animals utility in the the companion animals (Veterinary Science, 2017)
The electrocardiography is a diagnostic tool for the veterinary clinic of companion animals. In patients with cardiologic signs is the best non invasive means to evaluate the electric activity of the heart. It allows us to evaluate the present of arrhythmias, the pre-surgical state, assess the anaesthetic risk and check the pharmacologic treatments in cardiac patients amongst other. The objective of the present work was to illustrate the advantage of the electrocardiographic assess in canine and felíne patients, and its limitations and contraindications as well.